THE EFFECT OF INTERPERSONAL COMMUNICATION ON PERFORMANCE WITH WORK MOTIVATION AS A MEDIATING VARIABLE - Hezty Wahyu Utami Miskansidi; Roby Sambung; Olivia Winda Ony Panjaitan (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This study aims to provide an empirical explanation of the effect of interpersonal communication on performance with work motivation as a moderating variable at the interpersonal communication on performance with work motivation as a moderating variable at the Lamandau Regency Fire Department. Design/Methodology/Approach – The type of research used in this research is quantitative. The unit of analysis in this research is the employees of the Fire Department (DAMKAR) of Lamandau Regency, totaling 35 people. The collected data were analyzed using the Structural Equation Modeling (SEM) approach using the Partial Least Square (PLS) approach, the software used was SmartPLS 3.0. While collecting data with a questionnaire. Findings – Interpersonal communication has a positive and significant influence on performance and work motivation, while work motivation also acts as a mediator that strengthens the impact of interpersonal communication on employee performance at the Lamandau Regency Fire Department. Conclusion and Implications – Effective interpersonal communication at the Lamandau Regency Fire Department directly improves employee performance and work motivation. Work motivation is also proven to contribute positively to performance improvement. In addition, interpersonal communication not only has a direct impact, but also indirectly affects performance through increased work motivation.